Experimental and Kinetic Modeling of Galactose Valorization to Levulinic Acid - Muhammad Mufti Azis; Rochmadi Rochmadi; Arief Budiman; Retno Ringgani (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Levulinic acid, a versatile chemical building block, was derived from C6-sugar galactose using sulfuric acid as the catalyst. Galactose is monosaccharide of polysaccharides constituent that is mostly contained in third generation biomass, macro-microalgae. It currently receives high attention to be a source of renewable feedstock. The effect of temperature, catalyst concentration and initial substrate loadings were studied for 60 min, in the temperature range of 150–190 °C, acid concentration of 0.25–0.75 M and initial substrate loading of 0.05–0.25 M. The highest levulinic acid yield of 40.08 wt% was achieved under the following conditions: 0.05 M galactose, 0.75 M acid concentration, 170 °C temperature, and 40 min reaction time. The kinetic model was developed by first order pseudo-irreversible reaction. The results showed that the proposed model could capture the experimental data well. These results suggested that galactose, derived from macro- and micro-algae, can potentially be converted and applied for platform chemicals. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).